Firm-Size Wage Differentials in Switzerland: Evidence from Job-Changers - Winter-Ebmer, Rudolf; Zweimüller, Josef (American Economic Review, 1999)
Using information on job changes and search behavior of workers and controlling for endogenousnmobility we study firm-size wage differentials in Switzerland. We find that the observed crosssectionalnfirm size premium cannot be explained exclusively by worker heterogeneity. Almost 50n% of the cross-section differential is a firm-size effect.